BUILDING DEMOCRACY OF CULTURE IN SCHOOL THROUGH JURISPRUDENTIAL INQUIRY - Muhammad Japar; Dini Nur Fadhillah; Yuyus Kardiman; Yasnita Yasnita; Sarkadi Sarkadi (Universitas Negeri Yogyakarta, 2018)
This study was aimed at developing democratic culture in high schools through Jurisprudential Inquiry. The study used a descriptive qualitative approach by observing the planting of democratic values applied in the subjects of Citizenship Education by applying the jurisprudential inquiry learning model. The jurisprudential inquiry learning model empirically had built a dynamic learning atmosphere. This model provided opportunities for students to disagree but based on the accurate data and no need to be ashamed or inferior to acknowledge that the opinions of other students were better and they were willing to support that opinion. Thus, this model allows constructive debate. This practice was able to build values of respect for differences of opinion in the learning process. The results show that the jurisprudential inquiry learning model can be an alternative model in developing a democratic culture. Democratic values applied were actively participating in school activities, respecting diversity, familiarizing deliberations and maintaining a balance between rights and obligations in school.MEMBANGUN BUDAYA DEMOKRASI DI SEKOLAH MELALUI JURISPRUDENTIAL INQUIRYAbstrakPenelitian ini bertujuan mengembangkan budaya demokrasi di Sekolah Menengah Atas melalui Jurisprudential Inquiry. Pendekatan penelitian yang digunakan adalah pendekatan kualitatif deskriptif dengan mengamati penanaman nilai-nilai demokrasi yang diterapkan dalam mata pelajaran Pendidikan Kewarganegaraan dengan menerapkan model pembelajaran jurisprudential inquiry. Model pembelajaran jurisprudential inquiry secara empirik telah membangun atmosfer pembelajaran yang dinamis. Model ini memberikan peluang bagi siswa untuk berbeda pendapat tetapi berdasarkan data yang akurat dan tidak perlu malu atau rendah diri untuk mengakui bahwa pendapat siswa yang lain itu lebih baik dan rela mendukung pendapat itu. Dengan demikian, model ini memungkinkan terjadinya perdebatan yang kontruktif. Praktik ini mampu membangun nilai menghargai perbedaan pendapat dalam proses pembelajaran. Hasil penelitian ini menunjukkan bahwa model pembelajaran jurisprudential inquiry dapat menjadi model alternatif dalam mengembangkan budaya demokrasi yaitu berpartisipasi aktif dalam kegiatan sekolah, menghargai keragaman, membiasakan musyawarah dan menjaga keseimbangan antara hak dan kewajiban di sekolah.